Antibacterial activity of Rhynocoris marginatus (Fab.) and Catamirus brevipennis (Servile) (Hemiptera: reduviidae) venomS against human pathogens - Sahayaraj,K. (2006)
The reduviid predators Rhynocoris marginatus (Fab.) and Catamirus brevipennis (Servile) use their venoms to paralyze their preys. We detected the antibacterial activity of R. marginatus and C. brevipennis venoms against seven Gram-negative and four Gram-positive bacteria by using the disc diffusion method. Rhynocoris marginatus venom exhibited antibacterial activity against four Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa, Proteus vulgaris, Salmonella typhimurium) and one Gram-positive (Streptococcus pyogenes). Catamirus brevipennis venom showed antibacterial activity against six Gram-negative (Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Klebsiella pneumoniae, Proteus vulgaris, and Salmonella typhimurium) and three Gram-positive (Bacillus subtilis, Staphylococcus aureus, and Bacillus sphaericus) bacteria. Both C. brevipennis (90.91%) and R. marginatus (45.45%) venoms were more effective against Gram-negative bacteria (80% and 70% for R. marginatus and C. brevipennis, respectively). The venoms of both reduviid predators are composed of low molecular weight proteins (7-33 kD).